EDUKASI BAHASA INDONESIA YANG SANTUN DI MEDIA SOSIAL BAGI SISWA SEKOLAH MENENGAH PERTAMA - Irwan; Rezeki, Tri Indah; Sagala, Rakhmat Wahyudin; Rabukit (Jurnal Pengabdian Indonesia (JPI), 2025)
The development of digital technology has transformed communication patterns among young people, particularly through social media. However, the use of the Indonesian language by junior high school students in digital spaces often neglects linguistic norms and lacks politeness. This community service project aimed to educate students of SMPIT Al-Hijrah 2 Deli Serdang on how to use Indonesian properly, accurately, and politely in digital communication. The method involved initial observation, development of a contextual learning module based on social media content, implementation of interactive training, and follow-up evaluation and mentoring. The results indicate a significant improvement in students’ understanding of language norms and online communication ethics. Students became more aware in choosing appropriate diction, composing grammatically correct sentences, and maintaining polite interactions in social media posts and comments. Post-training mentoring also showed consistency in the students’ application of polite language in their digital interactions. This program demonstrates that language education integrated with digital literacy and character-building can shape ethical and productive communication behaviors among junior high school students. Such education is recommended to be continuously implemented as part of school literacy programs.